Prevalence of tablet splitting in a Brazilian tertiary care hospital - Vivianne V. Melo; Gessyka R. Pereira; Amanda Q. Soares; Izabel C. Silva; Stephania F. Taveira; Marcílio Cunha-Filho; Ricardo N. Marreto (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Background: Although a highly common practice in hospital care, tablet splitting can cause dose variation and reduce drug stability, both of which impair drug therapy. Objective: To determine the overall prevalence of tablet splitting in hospital care as evidence supporting the rational prescription of split tablets in hospitals. Methods: Data collected from inpatients' prescriptions were analyzed using descriptive statistics and used to calculate the overall prevalence of tablet splitting and the percentage of split tablets that had at least one lower-strength tablet available on the market. The associations between the overall prevalence and gender, age, and hospital unit of patients were also assessed. The results of laboratory tests, performed with a commercial splitter, allowed the calculation of the mass loss, mass variation, and friability of the split tablets. Results: The overall prevalence of tablet splitting was 4.5%, and 78.5% of tablets prescribed to be split had at least one lower-strength tablet on the market. The prevalence of tablet splitting was significantly associated with the patient's age and hospital unit. Laboratory tests revealed mean values of mass loss and variation of 8.7% (SD 1.8) and 11.7% (SD 2.3), respectively, both of which were significantly affected by the presence of coating and scoreline. Data from laboratory tests indicated that the quality of 12 of the 14 tablets deviated in at least one parameter examined. Conclusions: The high percentage of unnecessary tablet splitting suggests that more regular, rational updates of the hospital's list of standard medicines are needed. Also, inappropriate splitting behavior suggests the need to develop tablets with functional scores.